Analiza ročno izvedene inventure knjižničnega gradiva v Narodni in univerzitetni knjižnici - Gorkič, Polona (Knjižnica, 2014)
The National and University Library carried out a partial manual stocktaking in the years from 2010 to 2014. The materials were first verified against a computer-generated list of call numbers and then analysed using the catalogues. The analysis has not been completed yet. The examination of the bookstock took place at the dislocated storage building at Leskoškova cesta and included monographic publications only. The paper relays the experiences of librarians who took part in the stocktaking and its analysis. Statistical data were gathered reflecting the current state of the library stock. The emphasis is on the analysis, since it presents certain difficulties that result either from human fallibility or system errors. On the basis of the examination and analysis of the materials it was found that an automated stocktaking would be simpler and more effective, therefore it might be worth giving consideration to investing in the equipment required. The paper also points out the importance of consistency when performing the stocktaking, as it cannot be carried out properly and with certain degree of quality if the librarians involved are not both experienced and precise.
Keywords: inventura; knjižnične evidence; stocktaking; retrospektivna katalogizacija; catalogues; COBISS; COBISS.net; retrospective cataloguing